AI Ethics in Higher Education: Insights from Africa and Beyond - Corrigan, Caitlin C.; Asakipaam, Simon Atuah; Kponyo, Jerry John; Luetge, Christoph (SpringerBriefs in Ethics, 2023)
This open access book tackles the pressing problem of integrating concerns related to Artificial Intelligence (AI) ethics into higher education curriculums aimed at future AI developers in Africa and beyond. For doing so, it analyzes the present and future states of AI ethics education in local computer science and engineering programs. The authors share relevant best practices and use cases for teaching, develop answers to ongoing organizational challenges, and reflect on the practical implications of different theoretical approaches to AI ethics. The book is of great interest to faculty members, researchers, and students in the fields of artificial intelligence, computer science, mathematics, computer engineering, and related areas, as well as higher education administration.